Successful Treatment of Plasma Cell-Rich Acute Rejection Using Pulse Steroid Therapy Alone: A Case Report - Yo Komatsuzaki; Yasuyuki Nakada; Izumi Yamamoto; Mayuko Kawabe; Takafumi Yamakawa; Ai Katsuma; Haruki Katsumata; Aki Mafune; Akimitsu Kobayashi; Yusuke Koike; Hiroki Yamada; Jun Miki; et al. (Case Reports in Transplantation)
Despite the recent development of immunosuppressive agents, plasma cell-rich acute rejection (PCAR) has remained refractory to treatment. Herein, we report an unusual case of PCAR that responded well to pulse steroid therapy alone. A 47-year-old man was admitted for a protocol biopsy three months after kidney transplantation, with a stable serum creatinine level of 1.6 mg/dL. Histological examination showed focal aggressive tubulointerstitial inflammatory cell infiltration of predominantly polyclonal mature plasma cells, leading to our diagnosis of PCAR. Three months following three consecutive days of high-dose methylprednisolone (mPSL) therapy, an allograft biopsy performed for therapy evaluation showed persistent PCAR. We readministered mPSL therapy and successfully resolved the PCAR. Although PCAR generally develops more than six months after transplantation, we diagnosed this case early, at three months after transplantation, with focally infiltrated PCAR. This case demonstrates the importance of early diagnosis and prompt treatment of PCAR to manage the development and severity of allograft rejection.